Haplotype estimation for biobank-scale data sets - O'Connell, J; Sharp, K; Shrine, N; Wain, L; Hall, I; Tobin, M; Zagury, J; Delaneau, O; Marchini, J (Nature Publishing Group, 2016)
The UK Biobank (UKB) has recently released genotypes on 152,328 individuals together with extensive phenotypic and lifestyle information. We present a new phasing method, SHAPEIT3, that can handle such biobank-scale data sets and results in switch error rates as low as ∼0.3%. The method exhibits O(NlogN) scaling with sample size N, enabling fast and accurate phasing of even larger cohorts.